Model Intervensi Tiga Pilar Sebagai Upaya Menurunkan Prevalensi Stunting di Tanggul Kulon - Aji Seto Arifianto; Aqshal Nur Ikhsan; Syahmi Naufal Saputra; Nandita Putri Hanifa Jannah; Muhammad Rayasya Dziqi Cahyana; Rusdiarti Rusdiarti; Stephani Nesya Renamastika; Hendra Yufit Riskiawan; Syamsul Arifin; Ely Mulyadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Stunting in Tanggul Kulon Village, Jember, is a critical issue that negatively affects children’s health and cognitive development. Survey and interview results indicate that 2.71% of toddlers are identified as stunted. This condition is influenced by several factors, including limited knowledge about the importance of exclusive breastfeeding as a preventive measure, the lack of easy-to-use, automatic, and accurate anthropometric monitoring tools, and the need for alternative complementary foods that can address nutritional deficiencies in toddlers. This community service program implements a holistic three-pillar intervention. The methods used include: (1) Educational Intervention, through counseling on the importance of exclusive breastfeeding; (2) Technological Intervention, through the development and implementation of an Internet of Things-based anthropometric measurement device integrated with a mobile application for real-time monitoring; and (3) Nutritional Intervention, through hands-on training in producing healthy and nutritious cookies, which have undergone laboratory proximate analysis as supplementary food for toddlers.The results show that the implementation of the IoT system and the cookie-making training was successful, accompanied by capacity building for 18 Posyandu cadres and nutrition education for 90 families. These efforts provided direct benefits to around 200 toddlers and their parents, who now have access to more accurate growth monitoring. The interventions contributed to a reduction in stunting cases during the program, achieving a decrease of 29.63%. In conclusion, the integrated synergy between nutrition education, technological innovation, and food-based interventions has produced a comprehensive, measurable, and sustainable stunting-reduction model that can serve as a replicable reference for addressing similar issues in other communities